2013
DOI: 10.1016/j.neuron.2013.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Functional Maps of Visual Inputs to the Tectum

Abstract: Due to an oversight during manuscript preparation, the following equations were wrongly detailed within the Supplemental Information. The correct versions, which were used to generate the published data, are detailed below. This error has had no repercussions on the data as reported.(1) Vector sum magnitude and preferred orientations were derived from the average vector of responses (Swindale, 1998; Batschelet, 1981). For a set of N test orientations, x i , i = 0,1.NÀ1 which are uniformly distributed over 0-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
38
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 0 publications
9
38
0
Order By: Relevance
“…Each pixel corresponds to an area of 0.3 to 0.6 mm 2 , which is in the range of single presynaptic boutons of RGC axons [30]. We compared the pixel responses to dark versus bright looming by subtracting each pixel's bright looming response from its dark looming response.…”
Section: Pixelwise Analysis Reveals a Generalized Off Response Of Rgcmentioning
confidence: 99%
“…Each pixel corresponds to an area of 0.3 to 0.6 mm 2 , which is in the range of single presynaptic boutons of RGC axons [30]. We compared the pixel responses to dark versus bright looming by subtracting each pixel's bright looming response from its dark looming response.…”
Section: Pixelwise Analysis Reveals a Generalized Off Response Of Rgcmentioning
confidence: 99%
“…Moreover, the results of our recent experiments performed in carp and roach indicated that DS GCs of these¯shes also coincide with retinal DS units of C. gibelio (Maximova, personal communications). Results con¯rming our¯ndings have been published by Nikolaou et al (2012). Using calcium imaging techniques they recorded visually evoked activity of the retinal GC axons innervating tectum of zebra¯sh.…”
Section: Direction-selective Circuitry In The¯sh Retinamentioning
confidence: 99%
“…3) Precise spatial information is retained, both in the arrangement of neuronal cell bodies, and fine structural organization in neuropil (Ohki et al, 2005;Komiyama et al, 2010;Nikolaou et al, 2012). 4) Subcellular signaling can be resolved, allowing the measurement of both spatial aspects of dendritic processing (Borst and Egelhaaf, 1992;Svoboda et al, 1997;Euler et al, 2002;Hill et al, 2013) and the topography of synaptic inputs (Baden and Hedwig, 2007;Bollmann and Engert, 2009;Peron et al, 2009;Hopp et al, 2014).…”
Section: Identifying the Circuits Underlying Behaviorsmentioning
confidence: 99%
“…Functional studies revealed that RGCs sensitive to different directions of whole-field motion target different tectal sublaminae (Gabriel et al, 2012;Nikolaou et al, 2012), and that neurons in the tectum integrate these inputs to generate distinct tuning characteristics (Hunter et al, 2013).…”
Section: Selected Zebrafish Contributions To Systems and Circuits Neumentioning
confidence: 99%